The effect of advanced hybrid closed loop system on glycated hemoglobin (HbA1c) in a young male with type 1 diabetes mellitus and growth hormone treatment: A case report. Issue 8 (24th August 2021) - Petrovski, Goran; Al Khalaf, Fawziya; Campbell, Judith; Hussain, Khalid; Day, Emma; Pasha, Maheen
Abstract: The advanced hybrid closed loop system MiniMed 780G can be an effective tool to improve glycemic control and decrease the health burden in a young male with type 1 diabetes and short stature. Abstract : The advanced hybrid closed loop system MiniMed 780G can be an effective tool to improve glycemic control and decrease the health burden in a young male with type 1 diabetes and short stature.